Examining the influence of tax fairness on tax compliance in Libya - Ruhoma, Al Seddiq Alshadli Amhemed (2015)
The purpose of this study is to investigate the influence of tax fairness on tax compliance in Libya. Mansour, Mitra, Sdralevich and Jewell (2015) mentioned that the tax system in Libya is not fair and there is a need to design a tax system based on the principle of fairness. Therefore, this study puts emphasis on determining the impact of tax fairness dimension, such as general fairness, tax rate, exchange with government, attitude towards taxes of the wealthy and self-interest on tax compliance in Libya. This study will add to the body of knowledge related to tax compliance behaviour of taxpayers in Libya, especially since very little is known about this in the context of Libya. This study can help policy-makers to device a fair tax system that can help taxpayers as well as tax collection agency to make the system more efficient. The sample of the study comprises of taxpayers in Tripoli city. Data was analysed using SPSS. The findings of the present study show a significant relationship between tax fairness dimensions and tax compliance. This finding means that fairness of the tax system can enhance the level of tax compliance by a significant level. The government should hence device a fairer tax system to increase the level of tax compliance